2015
DOI: 10.1515/helmin-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transgenic insect-resistant maize to the community structure of soil nematodes in two field trials

Abstract: SummaryThe aim of this study was to determine the effects of Bt maize hybrid cultivation on soil nematode communities in two field trials, as well as to analyse other factors (fertilisation and moisture) responsible for the community structure of soil nematodes. Nematode communities were studied in maize plots at the locality of Borovce in western Slovakia. During 2012 and 2013, hybrids DK440 and DKC3871 (conventional) or DKC4442YG and DKC3872YG (Bt maize, event MON810) were sown in 10 repetitions each. Nemato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…The results in this study showed no significant differences on the composition, species richness ( S ), Shannon–Wiener diversity index ( H′ ), evenness index ( J ), Simpson’s dominant concentration ( C ), community similarity and ecosystem functioning composition of the NTAs community between transgenic insect-resistant maize (SK12-5 transgenic Cry1Ab/2Aj ) and the non-GE maize. These results are consistent with previous studies showing that Bt maize producing Cry1Ab [ 18 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], Cry1Ab and Cry2Ab [ 45 ], Cry1A.105 and Cry2Ab [ 46 , 47 ], Cry1Ac [ 48 , 49 , 50 ], Cry1A.105 and Cry2Ab and Cry3Bb [ 51 ], Cry1Ab and Cry1Ac [ 52 ], Cry1Ab and VIP3A [ 53 ], Cry1F [ 54 , 55 , 56 ], Cry1Ah [ 57 ], Cry1Ie [ 58 , 59 , 60 ], Cry34Ab1 and Cry35Ab1 [ 55 , 61 ], Cry34Ab1 and Cry35Ab1 and Cry1F [ 55 , 61 ], Cry3Bb [ 62 , 63 , 64 , 65 ] and VIP 3A [ 66 ] insecticidal proteins did not affect populations of NTAs in the field. Similarly, there were no significant effects detected in the majority of such filed experiments with Bt cotton and Bt rice [ 37 , 67 , 68 , 69 ].…”
Section: Discussionsupporting
confidence: 93%
“…The results in this study showed no significant differences on the composition, species richness ( S ), Shannon–Wiener diversity index ( H′ ), evenness index ( J ), Simpson’s dominant concentration ( C ), community similarity and ecosystem functioning composition of the NTAs community between transgenic insect-resistant maize (SK12-5 transgenic Cry1Ab/2Aj ) and the non-GE maize. These results are consistent with previous studies showing that Bt maize producing Cry1Ab [ 18 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ], Cry1Ab and Cry2Ab [ 45 ], Cry1A.105 and Cry2Ab [ 46 , 47 ], Cry1Ac [ 48 , 49 , 50 ], Cry1A.105 and Cry2Ab and Cry3Bb [ 51 ], Cry1Ab and Cry1Ac [ 52 ], Cry1Ab and VIP3A [ 53 ], Cry1F [ 54 , 55 , 56 ], Cry1Ah [ 57 ], Cry1Ie [ 58 , 59 , 60 ], Cry34Ab1 and Cry35Ab1 [ 55 , 61 ], Cry34Ab1 and Cry35Ab1 and Cry1F [ 55 , 61 ], Cry3Bb [ 62 , 63 , 64 , 65 ] and VIP 3A [ 66 ] insecticidal proteins did not affect populations of NTAs in the field. Similarly, there were no significant effects detected in the majority of such filed experiments with Bt cotton and Bt rice [ 37 , 67 , 68 , 69 ].…”
Section: Discussionsupporting
confidence: 93%